Implementation of a Positive Technology Application in Patients With Eating Disorders: A Pilot Randomized Control Trial - Enrique, Angel; Bretón-López, Juana; Molinari, Guadalupe; Roca, Pablo; Llorca, Ginés; Guillén, Verónica; Fernández-Aranda, Fernando; Baños, Rosa M.; Botella, Cristina (Frontiers in Psychology, 2018)
Background: Positive psychological interventions (PPIs) have been suggested to produce benefits in patients with eating disorders (ED) by improving well-being, which might act as a buffer of the harmful effects caused by the disorder. Best Possible Self (BPS) is a PPI which consists of writing and envisioning a future where everything has turned out in the best possible way. In this regard, positive technology can be of considerable benefit as it allows to implement specific PPIs that have already shown efficacy. Objective: This study tested the preliminary efficacy of the BPS exercise implemented through a positive technology application and carried out for one month, in improving positive functioning measures, compared to a control condition, in patients with ED. Follow-up effects were also explored at one and three months later. Methods: This is a pilot randomized controlled trial, with two experimental conditions. Participants were 54 outpatients, who were receiving ongoing specialized treatment in eating disorder services. 29 participants were randomly allocated to the BPS intervention and 25 to the control exercise. The sample was composed mostly by females and the mean age was 27 years. In the intervention group, participants had to write about their BPS. In the control group participants had to write about their daily activities. The exercise was conducted through the Book of Life, which is a positive technology application that allows users to add multimedia materials to the written content. Measures of future expectations, affect, dispositional optimism, hope and self-efficacy were assessed at different time frames. Results: Findings showed that all participants improved over time and there were no statistically significant differences between conditions on the specific measures. These effects were not influenced by prior levels of ED severity. Within-group effect sizes indicate a greater benefit for the participants in the BPS condition, compared to the control condition, on nearly all the measures. Conclusions: Results indicated that positive technology produced modest improvements in patients with eating disorders that are receiving current treatment for ED. More empirical attention is needed to explore the potential benefits of PPIs as supporting tools in the prevention and treatment of eating disorders.